A utility maximisation problem on multiple time scales. Issue 1 (10th February 2011) - Atici, Ferhan M.; Biles, Daniel C.; Lebedinsky, Alex
In this paper, we present a technique for a dynamic optimisation problem in which the value function and constraints can be on different time scales. Using this technique we solve a perfect-foresight utility maximisation problem for a finitely-lived consumer while making very general assumptions about timing of consumption and investing decisions.